METODE PEMAHAMAN HADIS (Analisis Mukhtalif al-Hadis) - Habieb Bullah (Universitas Islam Negeri Alauddin, 2022)
The Hadith of the Prophet is the second source of Islamic law after the Qur'an. Many problems of Islamic law are mentioned globally by the Qur'an, but the Prophet's hadiths detail these problems so that they can be understood by Muslims. The Hadith of the Prophet not only have an explanatory function for the Qur'an but also become an additional source of Islamic law that provides complementary laws to the laws contained in the Qur'an. Therefore, Muslims are very concerned about the validity of the Prophet's Hadith. One of the roles of the ulama is contained in the problem of contradicting hadiths (mukhtalif hadith). Are there any contradictions in the hadith of the Prophet? What is meant by mukhtalif and mushkil hadith? Since when did the problem of ikhtilaf hadith arise? What are the factors that cause ikhtilaf in hadith? What are the solutions offered by scholars to resolve these contradictions? Answering this question, the author tries to explain a little about the hadith that contradicts other hadiths. Therefore, the scholars try to seriously explain the traditions of the Prophet and explain if there is an ikhtilaf so that the validity of the hadith is maintained properly and is not misused by certain parties who are ignorant (do not know) so as not to harm Islam. This study uses a descriptive-analytic method which includes an analysis of the intent of the problem of ikhtilaf hadith. Thus, this research produces a critical view regarding the understanding of hadith related to ikhtilaf al-hadith.